The effect of selective breeding and genetic manipulation on the microbiome surrounding maize roots - Noortje, Notenbaert (Kansas State University, 2018)
Maize (Zea mays L.) is a major staple crop whose wild ancestor was domesticated about 9,000 years ago (Beadle, 1939). Long-term breeding for more desirable traits ultimately resulted in the maize we see today. This long-term breeding likely impacted the processes within the rhizosphere of maize, however, to what extent is not well understood. This study examined the microbial communities between an inbred maize line (B73), a hybrid of two isogenic lines (B73xMo17), and two genetically modified maize hybrids (DKC63-55RIB and DKC64-69RIB) to determine if the plant’s ability to attract beneficial microbes changed with breeding. The hypothesis was that the isogenic cultivar forms better relationships with bacteria and fungi compared to the newer cultivars, especially in low P soil. It was also expected that the greater the difference between the cultivars the more distinct their soil microbiome. To test these hypotheses, experiments were conducted under greenhouse and field conditions. Analyses consisted of root staining to test symbiotic relationships, phospholipid fatty acid analysis (PLFA) for microbial communities, total plant and root biomass, and nutrient content to understand plant responses. Based on the field results, there was no impact on root and shoot biomass and nutrient content by differences in cultivar. Differences in cultivar did impact arbuscular mycorrhizal fungi (AMF) colonization, which decreased over time and depth for all. Soil AMF also saw a significant effect by cultivar. Other microbial groups were not impacted by cultivar, were greatest in the control, and decreased over time. Greenhouse results showed a cultivar by time interaction for root and shoot biomass. Soil P also impacted shoot biomass, but not root biomass. Shoot nutrient content was greater in high P soil, while roots only saw an impact for root P. No cultivar effect was found for soil microbial groups except for fungi, while all microbial groups were reduced in the control soil. Most soil microbial groups were also impacted by soil P as indicated by reduced concentrations in low P soil. AMF was the only microbial group that was not negatively impacted by limited soil P. In addition, all soil microbial groups increased over time, although fungi saw a decrease at R1. No significances were observed for percent AMF colonization.
Keywords: Maize; AMF colonization; Maize rootsSoil microbiome